A csehszlovák erődrendszer magyar határmenti szakasza - Suba, János (Közép-Európai Közlemények, 2017)
The building of the Czechoslovakian border fortresses started in 1935, when the German threat had already become obvious. The original location and construction plan was being modified continuously according to the changes in the threats to the country and the improvement of strategic concepts and the fortresses' plans based on them. There were no fortresses planned along the Polish and Romanian border of Czechoslovakia. The Hungarian segment of the fortress line was set from Ipolyság through Losonc, Rimaszombat and Rozsnyó and continued on the south of Kassa to Beregszász, closely following the border. The defensive line opposite the Hungarian border was situated on the southern slopes of the Upper Hungarian mountains. This segment of the fortress line was known as 'minor fortress line'. They were basically machine-gun nests, which provided complete protection from infantry fire and also, they offered reliable defense against light artillery. There were five standard types of fortresses in use which were significantly different from each other. This study reviews the elements, the location and use of this fortress system.